The frontlines of artificial intelligence ethics : human-centric perspectives on technology's advance - Hampton, Andrew J.; DeFalco, Jeanine A. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This foundational text examines the intersection of artificial intelligence, psychology, and ethics, laying the groundwork for the importance of ethical considerations in the design and implementation of technologically supported education, decision support, and leadership training. Exploring how AI can support expert, creative, and ethical decision making in both people and virtual human agents, this is essential reading for students, researchers, and professionals in artificial intelligence, psychology, ethics, engineering education, and leadership, particularly military leadership"--
Introduction / Andrew J. Hampton and Jeanine A. DeFalco -- Law and moral philosophy to center human dignity as an indicator of ethical AI : concerns, cultural touchpoints, paths forward / Ozlem Ulgen -- Flipping rocks and pointing out the bugs : invisible threats and data / Darian DeFalco -- Seeing the forest and the trees : AI bias, political relativity, and the language of international relations / Leah C. Windsor -- The truth in our ideas means the power to work : implications of the intermediary of information technology in the classroom / James Ness, Lolita Burrell, & David Frey -- Benefits and potential issues for intelligent tutoring systems and pedagogical agents / Lishan Zhang, Xiangen Hu, Frank Andrasik, Shuo Feng -- The only living boy in homeroom : how virtual classes and agents fundamentally change the learning experience / Andrew J. Hampton, Donald M. Morrison, & Brent Morgan -- J.A.R.V.I.S., What should I do now? Human virtual agents as a means to more ethical decision-making / Jeanine A. DeFalco and John Hart -- Ethical frameworks for cybersecurity : applications for human and artificial agents / F. Jordan Richard Schoenherr and Robert Thomson -- Deep Blue wants you : identifying and addressing sources of bias in AI systems to support human resources decisions / Aryn Pyke, F. Jordan Richard Schoenherr, Robert Thomson -- On the shoulders of giants : how the social sciences can help AI navigate its ethical dilemmas / Arthur C. Graesser and John Sabatini.
Keywords: Artificial intelligence -- Moral and ethical aspects; Artificial intelligence -- Social aspects; PHILOSOPHY / Ethics & Moral Philosophy; PSYCHOLOGY / General; PSYCHOLOGY / Applied Psychology